Microbial Control by High Pressure Processing for Shelf-Life Extension of Packed Meat Products in the Cold Chain: Modeling and Case Studies - George Katsaros; Petros Taoukis (Applied Sciences, 2021)
Vacuum packed Bratwurst type cooked sausages and sliced or cubed meat products that have limited shelf-life of few days in chilled storage were HP processed (5 min, 600 MPa, 25 °C) and stored at different temperatures (0–15 °C). Color, texture, and microbiological and sensory evaluation were kinetically studied for control and HP treated samples. HP treatment did not alter the color and texture of the treated samples when compared to untreated ones. Lactic acid bacteria were found to be the main spoilage index. The rates of microbiological and organoleptic deterioration were estimated, and their temperature dependence was modeled by the Arrhenius equation. An increase of their shelf life of five to eight times was estimated, compared to untreated ones. A sensory survey on HP treated cooked ham showed that the consumers could not distinguish differences between control and processed samples immediately after processing. Obtained results were used along with appropriate tools relevant to cold chain management to demonstrate that HP treated products are less perishable compared to control ones, allowing for short exposure to temperature deviations during transportation and storage. This has a positive impact on the reduction of the frequency of spoiled products before consumption, acting as a useful tool for the meat product’s loss and waste reduction.